Improvement in the blood compatibility of polyvinylidene fluoride membranes via in situ cross‐linking polymerization. (26th December 2018) - Nie, Shengqiang; Zeng, Jiazhou; Qin, Hui; Xu, Xiaolu; Zeng, Jia; Yang, Chunlin; Luo, Jun
Abstract : In this study, we have provided a highly efficient, convenient, and universal protocol for preparing polyvinylidene fluoride (PVDF) membranes with low blood contact activation via in situ cross‐linking copolymerization of 2‐hydroxyethl methacrylate (HEMA) and acrylic acid (AA) in a solution of PVDF. The modified membranes were prepared from PVDF solution by phase inversion technology. The composition and morphology of the modified membranes were confirmed by attenuated total reflectance‐Fourier transform infrared (ATR‐FTIR) spectroscopy, thermogravimetric (TG) analysis, and scanning electron microscopy (SEM). Protein adsorption, clotting time, and contact activation on the modified PVDF membranes were systematically studied, the results indicating that after the incorporation of AA and HEMA, the modified PVDF membranes possessed anticoagulant properties in addition to low contact activation of blood components when in contact with blood. Therefore, fluorinated PVDF membranes with surfaces enriched with carboxyl and hydroxyl groups possessed the potential for use in long‐term blood‐contacting devices.